Fatherhood : discourses of men who experience a closer and participative relationship in the children care - Carneiro, Liana Maria Rocha (2012)
Objective: to describe the male view about the fatherhood, from the speeches of men who experience a closer and participative relationship in the children care. Method: qualitative research with descriptive approach, carried out with seven men, fathers of infants assisted in a Family Health Center in the city of Fortaleza-CE, Brazil, from February to May 2011. For the data collection, we used participant observation, semi-structured interview script, audio recorder and field diary. The analysis was based on the technique Collective Subject Discourse, from the following research questions: in your opinion, what is be a father? And What is your opinion with regard to the involvement of the father in children care? It is noteworthy to note that the study complied with the ethical and legal aspects of researches involving human beings9, and the research project was approved by the Ethics Research Committee of the Universidade Federal do Ceará, under the protocol number 330/10. Results: the fathers believe that being a father is: responsibility, very good and be friend indeed. Regarding the participation of fathers in children care were considered: very good and to be a friend indeed. Conclusion: we can see that the meaning of being a father, has become increasingly widespread and diffuse. From the new historical process, the man has experienced the fatherhood differently from the traditional model, that is to say, in a more participative way and with a father-child relationship more effective.